Fracture of tough and stiff metallosupramolecular hydrogels. (June 2020) - Zheng, S.Y.; Yu, H.C.; Yang, C.; W. Hong; Zhu, F.; Qian, J.; Wu, Z.L.; Zheng, Q.
Abstract: The rapid developments of tough hydrogels have broadened the applications of gel materials in biomedicine and engineering fields, which recalls the fundamental understanding of the fracture behaviors of these tough, soft materials. Herein, we study the fracture behaviors of a Fe 3+ coordinated poly(acrylic acid- co -acrylamide) (P(AAc- co -AAm)) hydrogel through pure shear tests. We measure a material-specific length, called fractocohesive length L f, defined by the ratio of fracture energy to fracture work ( L f  =  Г / W f ). We show that L f scales several important lengths that characterize the fracture behaviors of the hydrogel, including the transition length of cut-sensitivity L c measured by stretching samples of various initial crack lengths to rupture, the increment of the crack length needed to attain the steady state L ss measured from the resistance curve, and the size of large deformation zone L i measured by the polarized microscopic image. We further show that the fracture of P(AAc- co -AAm) hydrogel is viscoelastic, as demonstrated by tensile and rheological tests at different deformation rates. This work gives an insight into the fracture behaviors of P(AAc- co -AAm) hydrogel and provides a methodology that should be applicable in characterizing the fracture behaviors of other tough materials. Graphical abstract: Image 1 Highlights: A material-specific length - fractocohesive length - is measured for a tough metallosupramolecular P(AAc- co -AAm) hydrogel. Fractocohesive length scales several other important lengths that characterize the fracture behaviors. The hydrogel shows viscoelastic fracture, which is associated with the coordination bonds with a characteristic lifetime.